Gender and trauma since 1900 - Michaels, Paula A., 1966-; Twomey, Christina (London, England : Zed Books, 2021)
"Is Trauma a transhistorical, transnational phenomenon? Gender and Trauma challenges the standard history that has led to our contemporary understanding of psychological trauma to answer this question, and to explore the impact of gender in the experience and understanding of emotional distress. Bringing together eleven case studies from all over the world, it draws on methods from history, gender and communication studies to consider how trauma has been understood over the 20th and 21st centuries. Encompassing histories from Australia, Britain, Indonesia, Italy, the Soviet Union, Timor Leste, the United States and Vietnam, these examples demonstrate how gender and trauma are inextricably linked, and how the term 'trauma' has evolved over time. With chapters on war, political repression, displacement, rape and childbirth, the cases showcased in this volume highlight two pivotal transformations across the 20th century. First, the transformation of the trauma sufferer from perpetrator to victim, and second, the increased understanding of psychological consequences of sexual assault and domestic violence. Together, these diverse stories yield a more nuanced picture of what trauma is, how we have understood it alongside gender in the past, and how this affects our understanding of it in the present"--
Gender and trauma since 1900 / Paula A. Michaels and Christina Twomey -- Trauma in post-First World War Italy: experiences, erasures and denials / Martina Salvante -- Trauma, child refugees and humanitarians in the Spanish Civil War and the Second World War: a case study of Esme Odgers / Joy Damousi -- Servitude, displacement and trauma: Jewish refugee domestics in Great Britain 1938-45 / Jennifer Craig-Norton -- 'Combat exhaustion' versus 'psychoneurosis': American psychiatrists and the terminology of war trauma during the Second World War / Rebecca Jo Plan -- POWS into citizens: repatriation, gender and the civil resettlement units in Great Britain / Elizabeth Roberts-Pedersen -- Soviet maternity care and competing narratives of trauma / Paula A. Michaels -- Trauma and sexual violence: narratives and cases in late twentieth-century Australia / Lisa Featherstone -- Embodied, psychological and gendered trauma in militarized Kampala (Uganda) / Benjamin Twagira -- 'The missing ones': Vietnamese diasporic memory and women's narratives of loss / Nathalie Huynh, Chau Nguyen -- Refiguring trauma: women's narratives of suffering in post-conflict Timor-Leste / Hannah Loney -- Changing the story: women and trauma in Australian narratives of mental illness / Katie Holmes.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Psychic trauma -- Case studies; Women -- Violence against -- Case studies; War -- Psychological aspects -- Case studies; Victims of violent crimes -- Case studies; General & world history; Electronic books